Exploring vaccination practices of midwives in British Columbia. Issue 3 (6th May 2021) - Bettinger, Julie A.; Rubincam, Clara; Greyson, Devon; Weissinger, Sandra; Naus, Monika
Abstract: Background: Registered midwives in British Columbia (BC) are primary health care practitioners for healthy people throughout pregnancy and for approximately 6 weeks postpartum. BC registered midwives are authorized to prescribe and administer certain vaccines to adults under their care during the perinatal period and hepatitis B vaccine to high‐risk newborns. However, little has been documented about their recommendations for, and administration of, prenatal and infant vaccinations. This study surveyed midwives currently practicing in British Columbia to understand their vaccination practices. Methods: An online survey was administered to the members of the Midwives Association of BC in spring 2018. Outcome measures were the proportion of midwives who discussed, recommended, and administered the following vaccines: influenza, varicella, rubella, and infant hepatitis B. The proportion of midwives who discussed and recommended infant vaccines was measured. Barriers to discussion, recommendation, and administration of vaccines were captured. Results: Sixty‐three percent of 108 respondents administered vaccines to their clients. Hepatitis B and rubella were the most frequent vaccines administered. Logistical concerns were the greatest barrier to vaccine administration. This was followed by the perception that vaccine administration is not within the scope of practice of midwives, especially for influenza vaccine. Midwives who administered vaccines were significantly more likely to discuss and recommend vaccines to their clients and their infants. Conclusions: The majority of BC midwives discuss, recommend, and administer vaccines to their clients. Our survey highlighted key areas to address to strengthen midwifery capacity to discuss, recommend, and provide prenatal and infant vaccines.